The Religious Economics of Crisis: The Papal Use of Liturgical Vessels as Symbolic Capital in Late Antiquity - Salzman, Michele R. (Religion in the Roman empire, 2019)
This paper explores the multiple meanings of the restoration of liturgical silver plate by the bishops of Rome after the sacks of Rome in 410, 455, and 472. The author argues that this act was of primary importance to the bishops of Rome as a key means of reestablishing their hegemony over Christian communities in the city after periods of upheaval. By replacing lost liturgical plate, the bishops of Rome performed the role of patron in lieu of the emperor or wealthy private donor. Certainly, the donation of silver and gold in sacred contexts in the classical pagan world provides precedents for this practice and for its interpretation. But the donation of liturgical vessels must be understood within its specific Christian context. Because the donation of liturgical vessels was part of the foundation of a late antique church, their replacement by the bishop was an act of refoundation of the community of the faithful. And owing to the centrality of sacralised eating and drinking in the Christian rite of the Eucharist, the bishop's replenishment of liturgical silver also offered the individual and the community the promise of salvation. Thus the donations of silver and gold liturgical plate by bishops demonstrate the multiple ways in which the wealth of the church operated as symbolic capital, allowing the bishops to reinforce their authority over the community of the faithful in response to crisis.